Enhancing in vitro micropropagation of Alternanthera reineckii Briq. using various light-emitting diodes, culture media and plant growth regulators - Ekin U.; Dogan M. (Kuwait Journal of Science)
In this study, the effects of various light treatments, growth regulators and culture media (agar-solidified and liquid) on in vitro propagation of Alternanthera reineckii Briq. Were evaluated. In in vitro experiments were used red, blue, and white LEDs alone and various combinations of red and blue LEDs. Different levels of 6-benzylaminopurine (BAP) and Kinetin (KIN), ranging from 0.25 mg/L to 1 mg/L, were introduced into the solid and liquid Murashige and Skoog (MS) basal medium. In solid culture, the highest number of shoots per explant (16.67 shoots/explant) was observed when utilizing a proportion of 1:2 red/blue LEDs in MS medium supplemented with 1 mg/L BAP. On the other hand, in the liquid culture, 15.13 shoots/explant were obtained with 1 mg/L BAP under a 2:1 red/blue LEDs configuration. During the experiments involving KIN, 10.42 shoots/explant were observed in the solid culture conditions with 1 mg/L of KIN under a lighting configuration of 1:2 red/blue LEDs. On the other hand, a total of 10.62 shoots/explant was attained in the liquid MS medium with 0.50 mg/L of KIN under a lighting configuration of 2:1 red/blue LEDs. As a result, LED lights were found to be better than fluorescent lights for multiple propagations of A. reineckii. Moreover, higher shoot numbers and longer shoots were achieved with red and blue LED light combinations. © 2024 The Authors